(untitled) (Medical Forum Monthly, 2023)
Objective: To assess oral health related quality of life and oral dysfunction after radiotherapy from baseline to the last week in patients treated with alone of combination of chemotherapy in squamous cell carcinoma patients. Study Design: Prospective study Place and Duration of Study: This study was conducted at the Department of Oral and Maxillofacial Surgery, Jinnah Postgraduate Medical Center, Karachi from July 2022 to June 2023. Methods: The study involved 80 oral cancer patients who were awaiting radiotherapy. Some of these patients might also receive chemotherapy in addition to radiotherapy. (OHRQOL was used for assessment of oral health related quality of life. SPSS version 23 was used for data analysis. Results: According to metastasis, lymph node was noted in 56.3% patients and systematic was noted in 36.3% patients. Radiotherapy was performed to 43.8% patients and chemo-radiotherapy was given to 56.3% patients. Dental treatments received before R.T to 52.5% patients. Comparison of health quality of life scores at baseline, last week and 3 month of post RT showed that the differences were statistically significant, (p<0.010). Conclusion: The Oral Health-Related Quality of Life (OHRQOL) of oral cancer patients tends to decline during the course of radiation therapy (RT), whether it's administered alone or in combination with chemotherapy. OHRQOL tends to improve three months after the completion of radiation therapy.